Grafting hyperbranched polyester on the energetic crystals: Enhanced mechanical properties in highly-loaded polymer based composites. (10th November 2019) - Zeng, Chengcheng; Lin, Congmei; Zhang, Jianhu; Liu, Jiahui; He, Guansong; Li, Yubin; Liu, Shijun; Gong, Feiyan; Yang, Zhijian
Abstract: The interfacial strength usually plays a key role for exhibiting great effects on mechanical performances. In this work, typical energetic crystal 1, 3, 5-triamino-2, 4, 6-trintrobenzene (TATB) was firmly coated by the strong adhesion of polydopamine (PDA), then two HBPs with fatty and aromatic structure were grafted onto the surface of TATB, by using the hydroxyl groups of the PDA layer as secondary reaction platform. Four highly-loaded polymer based energetic composites (solid loading was 95%) were prepared with fluoropolymer binders as substrate. The results showed that the surface of grafted samples with 0.5 wt% HBP was more easily wetted by non-polar liquid. Improved storage modulus and creep resistance properties were exhibited in polymer bonded explosives (PBXs). The static mechanical properties of tensile and compressive strength were increased significantly by 26.5% and 19.8%, respectively, due to the strong interfacial reinforcement of HBPs. Highlights: Successfully grafting hyperbranched polyester to energetic crystal for the first time. Mechanical properties of PBX effectively enhanced by hyperbranched polyester grafting. Interfacial reinforcement strategy can be extended to other highly loaded composites.